PENGARUH PENGENDALIAN INTERNAL YANG LEMAH PADA SIKLUS PERGUDANGAN TERKOMPUTERISASI TERHADAP PENYALAHGUNAAN ASET (STUDI KASUS PADA PT.XXX SURABAYA) - Aprilia, Radita Fitri (Jurnal Akuntansi AKUNESA, 2014)
Internal control is a process undertaken to achieve the goals of the organization that consists of a variety of policies, procedures, techniques, physical equipment, documentation, and humans. Internal control as the foundation for a company, because if the foundation is good then the company's performance is considered good. Internal control on PT.XXX?s inventory section of spare parts had ineffective internal control. With the implementation of internal control such that there can be misuse of assets or fraud within the company. Asset misappropriation or fraud may occur because computer systems are often error and weak control. Asset misappropriation or fraud is usually did by staff or employees of the inventory section. However, if the employee did misappropriation of asset or fraud then the employee directly incurred as a result of the company without having any warning. Key word : internal control, computer systems, asset misappropriation.